IMPLEMENTASI PENDEKATAN JOYFUL LEARNING DALAM MENINGKATKAN PEMBELAJARAN BERMAKNA: ANALISIS ONTOLOGIS DAN EPISTEMOLOGIS DALAM PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Tsaqiilaa Qurrata'ayun; Miftahul Haera; Intan Anisa Fauziah Azahra; Azfa Taqiyya; Muhamad Parhan (Jurnal Studi Pesantren, 2026)
This research examines the implementation of joyful learning approaches to enhance meaningful learning in Islamic Religious Education from ontological and epistemological perspectives. Using qualitative literature review methodology, the study analyzes how joyful learning strategies can transform abstract religious concepts into engaging educational experiences. Findings reveal that integrating tarbiyah, ta'lim, and ta'dib concepts with interactive teaching methods significantly improves student engagement and spiritual development. The epistemological framework combining bayani and burhani methods provides a comprehensive foundation for knowledge acquisition. Technology integration, humor-based teaching, and participatory activities demonstrate practical effectiveness in creating transformative learning environments. The study concludes that philosophically-grounded joyful learning approaches holistically prepare students to navigate 21st-century challenges while maintaining Islamic values.